PARADOKS DIGITALISASI DI TEMPAT KERJA PEMICU BORE-OUT DAN RENDAHNYA KEPUASAN KERJA KARYAWAN - Muhammad Fajri; Roza Elfira; Nelson Nelson (Jurnal Ekonomi Bisnis Kompetif, 2025)
The digital era demands that every company integrate technology into its work systems. Society 5.0, with its people-centered approach, advocates leveraging technology to achieve employee well-being. The reality on the ground suggests the opposite: digitalization is actually leading to employee bore-out, a phenomenon researchers call the "digitalization paradox." The study aims to uncover whether the implementation of digitalization for bank employees will lead to positive outcomes or instill bore-out. This phenomenological study examined 12 bank employees with varying positions, length of service, and ages. The analysis used interpretive phenomenological analysis with the aid of coding through NVIVO. The results show that, based on three dimensions of bore-out, digitalization diminishes the meaning of work because high efficiency creates unproductive free time. Employees feel the technology they use in their tasks is no longer suited to their capabilities, especially long-serving employees with extensive experience and knowledge. Employees admit their work is boring. Furthermore, an unclear promotion system increases employee sentiment due to the mismatch between expectations and reality. The findings demonstrate that the researchers' notion of the digitalization paradox requires alignment with job design and employee capacity to avoid the "bored-out" syndrome described in the study. These findings cannot be generalized, as the concept of "bored-out" is still premature. Further, in-depth and specific studies are needed to more comprehensively uncover this paradox.